Fabrication of binary metal substituted CdO with superior aptitude for dye degradation and antibacterial activity. Issue 6 (15th March 2021) - Rahman, Abdur; Aadil, Muhammad; Zulfiqar, Sonia; Alsafari, Ibrahim A.; Shahid, Muhammad; Agboola, Philips O.; Warsi, Muhammad Farooq; Abdel-Haliem, Mahmoud E.F.
Abstract: With the widespread increase in the emergence of antibiotic-resistant bacterial strains and extent of the water contamination by organic pollutants, a considerable effort is required for the development of effective and safe materials to treat infections and remove water pollutants. Herein, we have developed doped and co-doped cadmium oxide CdM1 M2 O (M1 = Mn, M2 = Al, Sr, Ba) nanostructures with antibacterial activity against three bacterial strains ( Staphylococcus aureus, Klebsiella pneumoniae, and Proteus vulgaris ) and photocatalytic activity against methylene blue dye under direct sunlight irradiation. A very inexpensive and simple wet chemical approach was employed to fabricate the doped and co-doped nanostructures. The results of the antibacterial tests on Klebsiella pneumoniae, Staphylococcus aureus, and Proteus vulgaris bacteria indicated that all the prepared nanostructures possessed superb antibacterial properties. The Cd1-(x+y) Mnx Aly O nanostructures exhibited excellent degradation efficiency with typical organic dye (methylene blue) within 1 h of direct sunlight irradiation. The efficient synergistic antibacterial and photocatalytic activities coupled with their recyclability demonstrated the potential of Cd1 -(x+y) Mnx Aly O nanostructures for practical use in polluted water remediation and environmental protection applications. The simple method used for synthesizing the nanostructures to enhance their antibacterial and photocatalytic activities can potentially be extended to fabricate other photocatalysts and antibacterial agents.